2020
DOI: 10.1101/2020.09.09.20191239
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Transmission Within Danish Households: A Nationwide Study from Lockdown to Reopening

Abstract: Background The Covid-19 pandemic is one of the most serious global public health threats in recent times. Understanding transmission of SARS-CoV-2 is of utmost importance to be able to respond to outbreaks and take action against spread of the disease. Transmission within the household is a concern, especially because infection control is difficult to apply within the household domain. Methods We used comprehensive administrative register data from Denmark, comprising the full population and all COVID-19 tests… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
58
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 27 publications
14
58
2
Order By: Relevance
“…Secondary attack rates were not significantly different when restricting to 38 studies 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 65 , 67 , 68 , 69 , 72 with low or moderate risk of bias (15.6%; 95%, 12.8%-18.5%) (eFigure 4 in the Supplement ). There were no significant differences in secondary attack rates between 21 studies in China 22 , 27 , 31 , 36 , 37 , 39 , 45 , 46 , 48 , 58 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 , …”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Secondary attack rates were not significantly different when restricting to 38 studies 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 42 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 54 , 55 , 56 , 57 , 60 , 62 , 63 , 65 , 67 , 68 , 69 , 72 with low or moderate risk of bias (15.6%; 95%, 12.8%-18.5%) (eFigure 4 in the Supplement ). There were no significant differences in secondary attack rates between 21 studies in China 22 , 27 , 31 , 36 , 37 , 39 , 45 , 46 , 48 , 58 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 70 , …”
Section: Resultsmentioning
confidence: 89%
“…We identified 54 relevant published studies that reported household secondary transmission, with 77 758 participants (eTable 1 in the Supplement ). 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 A total of 16 of 54 studies (29.6%) were at high risk of bias, 27 (50.0%) were moderate, and 11 (20.4%) were low (eTable 2 in the Supplement ). Lower quality was attributed to studies with 1 or fewer test per contact (35 studies [64.8%]), small sample sizes (31 [57.4%]), a...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations